2015
DOI: 10.1161/circulationaha.114.013215
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Stiffness in Patients With Heart Failure and a Preserved Ejection Fraction

Abstract: Background The purpose of this study was to determine whether patients with heart failure and a preserved ejection fraction (HFpEF) have an increase in passive myocardial stiffness and the extent to which discovered changes are dependent on changes in extracellular matrix fibrillar collagen and/or cardiomyocyte titin. Methods and Results Seventy patients undergoing coronary artery bypass grafting underwent an echocardiogram, plasma biomarker determination, and intra-operative left ventricular (LV) epicardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
470
4
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(517 citation statements)
references
References 80 publications
28
470
4
15
Order By: Relevance
“…Regarding to the magnitude of changes, previously published studies found similar differences as reported here. Increase in PEVK element phosphorylation (Ser-12742 in the rat sequence) was 31% in human HTN (45) and 23% in patients with dilated cardiomyopathy (26), being similar to the 32.6% in mRen2 rats as reported here. A more prominent change (ϳ70% decrease) in PEVK phosphorylation level was found in a different site within the PEVK region of titin (Ser-12884) in a metabolic model of HFpEF (19).…”
Section: Sd Mren2supporting
confidence: 87%
See 1 more Smart Citation
“…Regarding to the magnitude of changes, previously published studies found similar differences as reported here. Increase in PEVK element phosphorylation (Ser-12742 in the rat sequence) was 31% in human HTN (45) and 23% in patients with dilated cardiomyopathy (26), being similar to the 32.6% in mRen2 rats as reported here. A more prominent change (ϳ70% decrease) in PEVK phosphorylation level was found in a different site within the PEVK region of titin (Ser-12884) in a metabolic model of HFpEF (19).…”
Section: Sd Mren2supporting
confidence: 87%
“…PEVK Ser-12742 hyperphosphorylation was previously demonstrated in mice with transverse aortic constriction (22), in an old HTN dog model (18), as well as in human HF (17,26). Moreover, a recent translational work implicated the hyperphosphorylation of the very same site (Ser-12742) in human HFpEF (45). It suggested that a significant rise in collagen-and titin-dependent stiffness is paralleled by explicit changes in titin phosphorylation levels, e.g., hypophosphorylation of PKA/PKG sites in the N2-Bus element and PKC␣-dependent hyperphosphorylation at Ser-11878 (Ser-12742 in the rat) in the PEVK element.…”
Section: Sd Mren2mentioning
confidence: 86%
“…HF and chronic liver disease) 29, 30. Collagen‐dependent ventricular stiffness is increased in HFpEF 1, 2, 3, 4, 5. The cardiac extracellular matrix is predominantly composed of fibrillar collagen type I (85%) and type III (11%) 29.…”
Section: Discussionmentioning
confidence: 99%
“…It has several pathophysiological aspects including cardiac hypertrophy and interstitial fibrosis1, 2, 3, 4, 5 and/or impaired functional reserve of multiple organs, such as lungs, vessels, skeletal muscle, kidney, and liver 1, 2, 6. The abdominal compartment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac troponin T, alone or in combination with N‐terminal fragment of the prohormone of B‐type natriuretic peptide (NT‐proBNP), and products of collagen metabolism have been evaluated for identification of hypertensive patients at risk for HF 84, 85, 86, 87…”
Section: Aging Phenotypementioning
confidence: 99%